Impact of Trade Liberalisation on Economic Growth: South Africa's automotive perspective - Libazi, Nomfundo (Graduate School of Business (GSB), 2025)
This study examines the impact of trade liberalisation policies on the economic growth of South Africa's automotive industry within the context of international trade. The study aims to investigate the effects of trade openness policy on the automotive industry's development and economic growth. The study uses the Vector Error Correction Model (VECM) to examine the relationship between trade liberalisation and economic growth. Time series data from Q1 1992 to Q4 2021 is used for the study to reshape conventional theories and inspire further research. The findings reveal a negative correlation between trade openness and economic growth in the long-run despite increased exports due to liberalisation policies. Even when the study adjusts the lagged results from 6 to 2, the impact is the same. This correlation is attributed to workforce limitations and an underdeveloped local supplier base. Results are validated through diagnostic tests, displaying significant and robust evidence. Given the divergence in the findings, further research is needed to better understand the results. Policymakers should concentrate on skills and human capital development to improve the technical and absorption capability of the local market. Skills and human capital development ensure that industry benefits from technological diffusions flowing from international trade. Supportive industrial policies aligned with long-term liberalisation strategies can upgrade and capture a greater value-added share within value chains.